Translational profile of coding and non-coding RNAs revealed by genome wide profiling of ribosome footprints in grapevine - Zhen, Zhang; Dongying, Fan; Yue, Song; Lipeng, Zhang; Jingjing, Liu; Minying, Liu; Yuanyuan, Xu; Juan, He; Shiren, Song; Yi, Ren; Bin, Han; Chao, Ma (Frontiers in Plant Science, 2023)
Translation is a crucial process during plant growth and morphogenesis. In grapevine (Vitis vinifera L.), many transcripts can be detected by RNA sequencing; however, their translational regulation is still largely unknown, and a great number of translation products have not yet been identified. Here, ribosome footprint sequencing was carried out to reveal the translational profile of RNAs in grapevine. A total of 8291 detected transcripts were divided into four parts, including the coding, untranslated regions (UTR), intron, and intergenic regions, and the 26 nt ribosome-protected fragments (RPFs) showed a 3 nt periodic distribution. Furthermore, the predicted proteins were identified and classified by GO analysis. More importantly, 7 heat shock-binding proteins were found to be involved in molecular chaperone DNA J families participating in abiotic stress responses. These 7 proteins have different expression patterns in grape tissues; one of them was significantly upregulated by heat stress according to bioinformatics research and was identified as DNA JA6. The subcellular localization results showed that VvDNA JA6 and VvHSP70 were both localized on the cell membrane. Therefore, we speculate that DNA JA6 may interact with HSP70. In addition, overexpression of VvDNA JA6 and VvHSP70, reduced the malondialdehyde (MDA) content, improved the antioxidant enzyme activity of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD), increased the content of proline, an osmolyte substance, and affected the expression of the high-temperature marker genes VvHsfB1, VvHsfB2A, VvHsfC and VvHSP100. In summary, our study proved that VvDNA JA6 and the heat shock protein VvHSP70 play a positive role in the response to heat stress. This study lays a foundation for further exploring the balance between gene expression and protein translation in grapevine under heat stress.